Late presentation of lung adenocarcinoma in a stable solitary pulmonary nodule: A case presentation and review of the literature. (2020) - Aqsa, Anum; Droubi, Sami; Sharma, Dikshya; Maroun, Rabih
Abstract: A 67-year-old patient has been followed by our pulmonary clinic for Chronic obstructive pulmonary disease (COPD) and a stable pulmonary nodule. Solitary pulmonary nodule (SPN) was detected on the lung cancer screening by low dose computed tomography (CT) scan of the chest. It remained stable on repeat CT scan at 6, 12 and 24-months interval. Yearly lung cancer low dose CT scans of the chest showed stability of the SPN for 12 years. A mechanical fall necessitating trauma workup unveiled increase in size of the nodule from 4 mm to 11 mm within one year of the previous screening CT chest. Biopsy and Histopathology confirmed the diagnosis of lung adenocarcinoma. The patient then underwent right upper lobectomy followed by chemoradiation therapy. Current guidelines do not recommend follow up for a solitary pulmonary nodules less than 6 mm nodule if it remains stable for 12-24 months. Our case report of the late presentation of lung adenocarcinoma in a stable solitary pulmonary nodule suggests the need to exercise increased caution in the management of incidental pulmonary nodules.